Uji Pertumbuhan dan Produksi beberapa Varietas Padi dengan System Rice of Intensification pada Titik Tanam Berbeda - Utama, M. Zulman Harja; Misradelfita, Misradelfita; Ernita, Milda (Fakultas Pertanian Universitas Tamansiswa Padang, 2009)
Experiment was aimed to investigate the test growth and production of several rice variety with system rice of intensification on distance difference. Experiment was conducted in farmer land of Jorong Kampung Jambu Kenagarian Bayua, Tanjung Raya of Agam District, from April to August 2008. Experiment was conducted using random completed design of two factors. First factor was four applications of rice variety, mean while second factor was two distance difference. The results revealed that an addition of combination variety Cisadane with distance 10 cm give high success rate to growth and production, with yield 8.6 ton/ha